HUBUNGAN JAM KERJA DAN KARAKTERISTIK PERAWAT PELAKSANA DENGAN PENERAPAN SASARAN KESELAMATAN PASIEN PADA RUMAH SAKIT DI KOTA PADANG - Yessi Fadriyanti, Yosi Suryarinilsih (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Patient safety is now a global issue which is now being reported to the demands of patientson medical errors that occur in patients. Patient safety goals is a requirement to be implemented inall hospitals accredited by the Commission on Accreditation of Hospitals. Patient safety goals isexpected to prevent or reduce injury and improve patient safety pasien.Menurut report from IOM(Institute of Medicine) in 1999 Amarika openly stated that at least 44,000 and even 98,000 patientsdied in the hospital within one year as a result of medical errors (medical errors) which previouslycould have been prevented, this has resulted in lawsuits experienced increased hospital. This studyaims to determine the relationship of nurses working hours with the application of patient safetygoals. This type of research is a quantitative study, using cross-sectional study with a sample of 93people. Ways sampling with proportional random sampling. The results showed no significantrelationship between hours of work, length of work and knowledge of nurses with the applicationof patient safety goals. Variables related to the implementation of patient safety goals are age andeducation. The results of this study can be considered for admission to the hospital on new nursesneed to consider the age factor in early adulthood, lists the nursing staff who will participate incontinuing education and supervision to nurses related to patient safety.Keywords: patient safety, patient safety incidents